Analisis Efek Moderasi Familiaritas Merek Terhadap Hubungan Antara Frekuensi Menonton Dengan Sikap Atas Merek Pemirsa Dalam Strategi Penyisipan Produk Di Acara Televisi X Factor Indonesia - Hadiyanto, Inka Septin; Nurcaya, I Nyoman (E-Jurnal Manajemen; Vol 3 No 3 (2014), 2014)
The aim of this research is to know the effect of brand familiarity as moderating variable toward the relationship among movie viewing frequency with brand attitude audience in product placement strategy in television shows X Factor Indonesia. Respondent of this research are young people at least 15-25 years old and ever seen a television shows X Factor Indonesia. The number of respondents on this research defined 130 respondents by using sampling technique that is purposive sampling. This research used analysis of two ways ANOVA. The analysis finds that the movie viewing frequency variable not significantly influence the attitude of the brand audience, brand familiarity variables significantly influence the attitude of the brand audience, and there is a mutual influence or joint effect between the movie viewing frequency variable and , brand familiarity variables to the average attitude of the brand attitude audience.   Keyword : Product placement, movie viewing frequency, brand familiarity, and brand attitude.